EFFECTIVENESS OF CORPORATE GOVERNANCE PRACTICES IN AN INFRA ORGANIZATION - Pawar, I. Anand; Kuruba, Ganagappa (International Journal For Research In Business, Management And Accounting, 2020)
Corporate Governance (CG) is a principle as well as policy guidelines for promoting corporate fairness, transparency, and accountability in its business operations. It is pertinent to all sectors and industries and not an exception to Infrastructure Company. Therefore, an attempt has been made to measure the effectiveness of CG practices from its employees’ perspective and promote effective CG at GMR (Grandi Mallikarjun Rao) a leading infrastructure company in the industry as well as in the country. This study found that there is no difference of opinion among the Executives and Non-Executives of GMR towards its CG practices. However, corporate discipline, fairness and transparency as part of good CG should be improved further in order to boost up the stakeholders confidence.